Knowledge sharing programme with Majlis Profesor Negara at Lundu dan Sematan - Isnin, Nadrawina (Universiti Teknologi MARA, Sarawak, 2016)
The Knowledge Sharing programme with school students was implemented in Lundu and Sematan from 28 to 29 January 2016. This programme was under Majlis Profesor Negara for ICT Cluster headed by Yang Berbahagia Prof. Datuk Dr. Khairuddin Ab. Hamid and a team of professors from UTEM, Yang Berbahagia Prof. Dr. Ahmad Zaki b. Abu Bakar and Prof. Dr. Rabiah bt Ahmad and Yang Berbahagia Prof. Dato’ Dr. Teo Kok Seong from UKM. They were assisted by academicians, Prof. Dr. Narayanan from UNIMAS and Dr. Nadrawina Isnin and Madam Noorfadhleen Mahmud from the Faculty of Administrative Science and Policy Studies, UiTM Sarawak. The two-day programme was designed in such a way that the big groups of students were divided into two small groups. At SMK Lundu, the group comprised 300 students from Form 4 and Form 2 respectively while at SMK Sematan, the target groups were Form 1A with 32 students and Form 5 with 218 students.